Streptokinase treatment for femoral artery thrombosis after arterial cardiac catheterisation in infants and children. - Brus, F (1990)
Data on 205 children who underwent retrograde arterial catheterisation were studied to assess the frequency of femoral artery thrombosis and the safety and efficacy of systemic streptokinase treatment for this complication. In 29 (14%) a transarterial balloon dilatation was performed. In 15 (7.3%) patients impaired arterial perfusion due to vascular spasm with or without thrombus formation was seen in the cannulated leg after catheterisation. Despite heparinisation, signs of impaired arterial circulation persisted in nine patients (4.4% of the total). In these patients femoral artery thrombosis was strongly suspected. Six (53%) of these had undergone a balloon dilatation. Therefore in this study the risk of femoral artery thrombosis developing was 12 times greater after transarterial balloon dilatation than after arterial catheterisation without dilatation (20.6% v 1.7%). Systemic infusion of streptokinase was started in all patients with femoral artery thrombosis. Arterial perfusion became normal in all patients, though in one this was delayed. Haematological monitoring showed lengthening of the thrombin time and a decrease of the fibrinogen concentration during streptokinase treatment. There were no serious complications. Systemic infusion of streptokinase is a safe and useful treatment in children with persistent femoral artery thrombosis after arterial cardiac catheterisation.